Applied crisis management in the supply chain: a qualitative study - Coulson, Kirstyn, author; Mumford, Troy, advisor; Macdonald, John, committee member (Colorado State University. Libraries, 2025)
This thesis examines how supply chain leaders handle crisis and what effective leadership looks like. I conducted qualitative interviews with six leaders across manufacturing, logistics, procurement, healthcare, and rail. Their experiences point to several themes that shape crisis response, including the severity of the disruption, the vulnerabilities within a complex supply chain, and the leader’s own capabilities. Crises happen in every industry. They create financial risk, time pressure, and a need for strong coordination across teams. The leaders I interviewed described a shared approach. They stay outwardly steady while managing internal stress, pull people and resources together quickly, and turn each disruption into a learning opportunity through root cause analysis and prevention planning. A key takeaway is that a supply chain never leaves a crisis in the same condition it entered. Disruption exposes weak spots and moves the organization from a mindset focus on efficiency toward greater resilience. Overall, the research shows that effective crisis leadership relies less on technical expertise and more on emotional intelligence and a commitment to supporting teams through uncertainty.
Colorado State University College of Business, Concentrations in Supply Chain Management and Management and Innovation.
Keywords: crisis; supply chain; leadership